Study of Noise Level in Different Commercial Zones of Kathmandu City and Its Effects on Human Health - Rayamajhi, Kamana; KC, Ritika (Amrit Research Journal, 2025)
Noise refers to the presence of unwanted or excessive sound in the environment, arising from various sources such as transportation, industrial activities, commercial construction, and recreational activities. Unlike other forms of pollution that may be visible, noise pollution is invisible, making it silent yet potent threat. This study aims to determine the noise level in major commercial zones of Kathmandu City along with the health effects concerned. The study was conducted during the month of June 2025 for 12 days. The measurement of noise level was taken with the help of Sound Level Meter (SL-4010) in four different timeframes of the day i.e., 6-7 am in the early morning, 9-10 am in the morning, 1-2 pm in the afternoon, and 5-6 pm in the evening. The measurement was done for 10 minutes in the interval of 10 seconds. The study found that New Road had the highest equivalent noise level of 79.59 dB (A) whereas Thamel had the lowest average noise level of 63.93 dB (A). While assessing the health effect on the general public, major health effects were found to be headaches and irritation, hearing effects. Vehicles were the major sources of noise followed by people’s crowds, commercial construction and loudspeakers.